Revitalisasi Usaha Las Tradisional Menjadi Bengkel Las Kreatif melalui Inovasi Desain Metal Art dan Digitalisasi - Viola Malta Ramadhani; Riana Nurmalasari; Tuwoso (Al-DYAS, 2026)
Traditional welding businesses in Banjarsari Village, Madiun Regency, face challenges including low operational efficiency, high rates of welding defects, material and energy waste, and limited product variety, resulting in restricted market reach and low profit margins. This community service activity aims to revitalize and transform local welding businesses through metal art-based product diversification, technological modernization, and the digitalization of business management. The program was implemented in four stages: preparation through observation, interviews, and equipment procurement; implementation through the application of metal art and a smart welding system; evaluation through a review of revenue and program effectiveness; and follow-up through publication and reporting. The results indicate that the application of technology increased production capacity and product quality by stabilizing welding parameters, reducing defect rates, improving precision, and conserving energy and materials. Metal art-based product diversification supported by digital marketing strategies also successfully expanded market reach beyond the Madiun region. Thus, the integration of technological modernization, product diversification, and marketing digitalization can sustainably enhance competitiveness, broaden consumer segments, and strengthen the profit margins of welding business operators. This program provides a model for revitalizing traditional welding businesses that can be applied to promote the technology- and creativity-based transformation of local enterprises.